Role of c-Cbl–Dependent Regulation of Phospholipase Cγ1 Activation in Experimental Choroidal Neovascularization - Husain, Deeba (Association for Research in Vision and Ophthalmology, Inc., 2010)
PURPOSE. Activation of phospholipase Cγ1 (PLCγ1) by vascular endothelial growth factor receptor (VEGFR)-2 is necessary for proliferation and tube formation of endothelial cells in vitro. Previous work has demonstrated that Casitas B-lineage lymphoma (c-Cbl) promotes ubiquitination of PLCγ1 and suppression of its tyrosine phosphorylation. This study was designed to evaluate the importance of PLCγ1 and c-Cbl in experimental choroidal neovascularization (CNV). METHODS. The role of PLCγ1 was studied in three models of angiogenesis: the endothelial cell culture system, the chorioallantoic membrane (CAM) assay, and the laser-induced CNV model. Endothelial cells were analyzed for the role of PLCγ1 in promoting tube formation. CAMs were incubated with pharmacologic agents that either inhibit or stimulate PLCγ1. CNV was induced in wild-type and c-Cbl–knockout mice, and the progression of CNV was evaluated by fluorescein angiography. RESULTS. Activation of PLCγ1 was necessary for tube formation of endothelial cells. PLCγ1 stimulation increased the growth of blood vessels and conversely, PLCγ1 inhibition decreased the growth of blood vessels in the CAM model. CNV lesions in the c-Cbl–knockout mice were significantly greater in number, more confluent, and increased in size with time, compared with those in the control wild-type mice. CONCLUSIONS. The data show that PLCγ1 plays an important role in angiogenesis. Loss of c-Cbl results in enhanced CNV in the eye. The study also shows that c-Cbl plays an important role in ocular angiogenesis, suggesting that modulation of c-Cbl activity or inhibition of PLCγ1 would be a compelling target for antiangiogenesis therapy.